Some factors contributing to the paucity of yellow fever in the Ashanti Region of Ghana - Esena, Reuben Kwasi (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Philosophy in Clinical Microbiology.